Association of Escherichia coli pathotypes with fecal markers of enteropathy and nutritional status among underweight adults in Bangladesh - Sthity, Rahvia Alam; Islam, Md. Zahidul; Sagar, Md. Ehsanul Kabir; Gazi, Md. Amran; Ferdous, Jafrin; Kabir, Md. Mamun; Mahfuz, Mustafa; Ahmed, Tahmeed; Mostafa, Ishita (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionEnvironmental enteric dysfunction (EED), a subclinical intestinal disorder, is characterized by chronic fecal-oral exposure to entero-pathogens and could be diagnosed by measuring non-invasive biomarkers. Escherichia coli is the one of the key bacterial enteric pathogens that drives EED, but there is a lack of information on the E. coli pathotypes in relation to the biomarkers of EED in malnourished adults. Here, we intended to measure the possible association of these pathotypes with EED biomarkers and nutritional status of adults residing in a slum in Bangladesh.MethodFecal samples were collected from 524 malnourished adults (BMI ≤18.5 kg/m2) living in a slum-setting in Dhaka from March 2016 to September 2019 and analyzed by TaqMan Array Card assays to evaluate the presence of E. coli pathotypes and other entero-pathogens. The multivariable linear regression model was used to assess the association.ResultsIn these malnourished adults, the most prevalent pathotype of E. coli was EAEC (61.7%) and the least prevalent was STEC (6.7%). The prevalence of atypical EPEC, ETEC and Shigella/EIEC were 52%, 48.9% and 45.1% respectively. The infection with atypical EPEC had significant positive association with levels of Myeloperoxidase (b = 0.38; 95% CI = 0.11, 0.65; p-value = 0.006). Similarly, a significantly higher concentration of alpha-1-antitrypsin (b = 0.13; 95% CI = 0.03, 0.22; p-value = 0.011) was found in the STEC-infected adults. However, no notable association was found between the E. coli pathotypes and nutritional status of these adult participants. Moreover, Plesiomonas infected adults were more likely to be infected with EAEC (p-value = 0.017), ETEC (p-value <0.001) and STEC (pvalue = 0.002). Significant coinfection was also detected among the pathotypes and other entero-pathogens such as Giardia, Ascaris, Campylobacter, Salmonella, Enterocytozoon bieneusi, and Adenovirus.DiscussionThe study results imply that there is an influence of particular E. coli pathotypes (EPEC and STEC) on intestinal inflammation and gut permeability of the malnourished Bangladeshi adults, but no association with nutritional status is found. Potential pathogenicity of the E. coli pathotypes is also observed when co-infection with other pathogens exists in these adults.